Report of the Prohibition Enquiry Committee 1954-55 - Planning Commission (Planning Commission, 1954)
The Prohibition Enquiry Committee was appointed by the Planning Commission, Government of India, in pursuance of Resolution No. PC/Proh/1/54, Dated the 16th December 1954.
Planning Commission